Biomechanics for coaches: Key kinematic variables for the execution of high difficutly value Yurchenko vaults - Grande Rodriguez, I. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Vault is the most biomechanical studied gymnastics apparatus because it is the only in which gymnasts make only one skill (Sands et al., 2003). Group IV vaults (round off in or Yurchenko vaults) are the most repeated vaults executed in competitions (Kwon et al., 1990). Actual Code of Points (FIG, 2007) sets up that the Departure Score depends on A Score and B Score. The A Panel Judges score is only the Difficulty Value (DV) in vault. Difficulty Value of Group IV vaults changes since 3.80 p up to 6.50 p. So at similar execution level gymnasts who present a high DV vault have a significant advantage. The purpose of this study was to determinate the key kinematics variables for execute high DV Yurchenko vaults. 27 Yurchenko vaults of 7 Senior and Junior gymnasts of the Spanish National Team were filmed for 3D analysis. The springboard phase or punch (contact with the springboard), pre-flight (1st flight) and vaulting table support or repulsion phases were studied. We grouped the vaults in three categories: Level 1 (L1) (DV > 5.00 p): Yurchenko 1 12 twist and Yurchenko one twist (n=9). Level 2 (L2) (DV > 4.00 p): Yurchenko stretched vaults (n=9). Level 3 (L3) (DV > 3.50 p): Yurchenko tucked vaults (n=9). Variables were selected from technical aspects that coaches can correct in the training session instead of most common variables analyzed in other Yurchenko biomechanical studies. Temporal, angular, spatial and velocity variables were statistically analyzed. According to the ANOVA`s results between groups key variables for execute high DV Yurchenko vaults were: high horizontal velocity in board touch position, high middle pelvic waist vertical velocity at board take off, low angle between forearm and vaulting table at vaulting table touch position, high pelvic vertical and horizontal velocity at vaulting table touch position, high shoulders vertical velocity at vaulting table take off position. This variables have significant differences between level groups (p<0.05).